A remote-controlled robot-car in the TPS tunnel. (November 2019) - Lee, T Y; Chen, B Y; Hsu, T W; Huang, B Y; Lin, W Y; Kuo, C H
Abstract: A remote-controlled robot-car named "PhotonBot" was put into the TPS accelerator tunnel and is equipped with a 360 ° LiDAR for SLAM and navigation, two cameras for perception and first-person view, and a thermal imaging system. The robot can be remotely controlled and can send data to a remote PC through Wi-Fi. With SLAM, it can go more freely without being restricted to a designated path. In order to ensure it can work continuously, there is a wireless charging station in case of a low battery.